Phonognatha vicitra Sherriffs, 1928—a taxonomic misidentification of the orb-weaving spider Acusilas coccineus Simon, 1895 (Araneae, Araneidae) - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2018)
The species described as Phonognatha vicitra Sherriffs, 1928 is the only representative of the genus Phonognatha Simon, 1894 in India (World Spider Catalog 2018). The type locality of this species was a coffee estate named Charlotte estate/division, which is located adjacent to the Cauvery River in the Siddapura/ Sidapur village in the Kodagu (Coorg) district of the southwest Indian state of Karnataka (Sherriffs 1928). The species is still known from its original description, which is based on seven female specimens, and its male genitalia remained unveiled. For redescribing this species, we had visited the Charlotte estate/division and collected topotype materials of P. vicitra. However, while examining the materials, we found that the specimens from the Charlotte estate/division indeed belong to the South East Asian orb-weaving spider genus Acusilas Simon, 1895, indicating that Sherriffs misplaced his species in Phonognatha. In the present paper, we propose to transfer P. vicitra to Acusilas and synonymise it with Acusilas coccineus Simon, 1895.